Analysis Of Reading Difficulties In The Early Stages Among Second-Grade Students At SDN 2 Kayangan In The 2024/2025 Academic Year - Purnama, Dewi; Habiburrahman, Lalu; Taufik, M. (Peneliti.net, 2025)
This study aims to describe the analysis of students' difficulties in beginning reading in grade 2 students in elementary schools. students' difficulties in beginning reading in grade 2 students at Kayangan public elementary school in the 2025 school year. Kayangan public elementary school in the 2025 school year. This research focuses more on the difficulties of This is so that everyone knows that student difficulties in beginning reading are caused by several factors that cause reading difficulties, where in today's factors that cause reading difficulties, where in today's times students are still found to have difficulties in beginning reading. who have difficulty in beginning reading. This research is a descriptive qualitativedescriptive qualitative research with a case study type of research. Subjects in The subjects of this research are grade 2 students at SDN 2 Kayangan. The focus of this research on students who have difficulty in beginning reading in grade 2 students. The results of this study indicate that the difficulties faced by students in beginning reading at SDN 2 Kayangan, namely (a) students have difficulty in mentioning letters, (b) students have difficulty in distinguishing between letters, and (c) students have difficulty in distinguishing between letters. naming letters, (b) students have difficulty distinguishing similar letters, (c) students have difficulty spelling, and (d) difficulty in reading when there is a combination of consonant letters such as “b” and “c”. when there is a combination of consonant letters such as “ny and ng”. In addition, the factors that cause students to have difficulties in beginning reading at SDN 2 Kayangan namely (a) physiological factors or physical conditions (b) intellectual or intelligence students have low memory (c) psychological factors, namely motivation & interest (d) environmental factors such as (d) environmental factors such as the lack of role and attention of parents.